Phosphonium chloride induced dichlorosilylene transfer from trichlorosilane - Kang, SH; Han, JS; Lee, ME; Yoo, BR; Jung, IN (AMER CHEMICAL SOC, 2003)
Heating trichlorosilane with conjugated dienes or an acetylene solution at 150 or 180 degreesC in the presence of a catalytic quantity of tetrabutylphosphonium chloride resulted in elimination of HCl and dichlorosilylene transfer to the unsaturated substrates to afford silacyclopentenes or 1,4-disilacyclohexa-2,5-dienes, respectively, in good to excellent yields. The trapping reaction with hex-3-yne gave 1,1,4,4-tetrachloro-2,3,5,6-tetraethyl-1,4-disilacyclohexa-2,5-diene in 79% yield, and its structure was determined by X-ray crystallography.
Keywords: ALKYL-HALIDES; SILYLENE; HEXACHLORODISILANE; SILYLATION; CHEMISTRY